AUDIT OF PROGNOSTICATED FINANCIAL INFORMATION: PROBLEMS AND PERSPECTIVES OF DEVELOPMENT - Holyash, Iryna; Halushka, Nataliya (Journal of European Economy, 2017)
The paper studies theoretical issues and practical application of prognosticated financial information audit. The problems of that audit arrangement are considered, and the advantages of its introduction as well as the perspectives for its development are accentuated.